Return to play considerations for cervical spine injuries in athletes - Paulus, S.; Kennedy, D. J. (Physical Medicine & Rehabilitation Clinics of North America, 2014)
Injuries to the cervical spine during sports are relatively common, depending on the specific sport. Given the adjacent neurovascular structures, any injury to the cervical spine must be evaluated with caution to assess its severity. With proper management, most injuries resolve quickly and allow for rapid return to play (RTP). The purpose of this article is to synthesize the current literature on the most common cervical spine injuries in athletes, including injury prevalence, mechanisms of injury, and RTP decision-making processes.